Additional knowledge respecting taxonomy of the social wasp genus Ropalidia (Hymenoptera: Vespidae: Polistinae) from Vietnam, with new records of three species and an updated key to species - Bui, Hoa Thi Quynh; Tran, Ngat Thi; Bozdoğan, Hakan; Nguyen, Lien Thi Phuong (Zootaxa, 2020)
Species composition of social wasps of the genus Ropalidia from Vietnam is reported, with 24 species having been recorded. Of those, three species are newly recorded for the Vietnamese fauna, namely Ropalidia binghami van der Vecht, 1941, R. parartifex Tan & van Achterberg, 2014 and R. variegata (Smith, 1852). The presence of R. sumatrae (Weber, 1801) in Vietnam is confirmed. An updated key to all recorded species of the genus Ropalidia from Vietnam is also provided.